2015
DOI: 10.15835/nsb739532
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Magnetic Treatment of Irrigation Water on the Growth and Yield of Tomato

Abstract: This study was carried out to determine whether magnetic treatment of the irrigation water may actually enhance vegetative growth and yield of tomato. Three magnetic flux densities of 124, 319 and 719 G (treatments T1, T2 and T3) were used to treat the water and a control experiment (Tc) which was irrigated with non-magnetically treated water was also set up. The magnetic field was produced by an electromagnet that had a variable voltage unit varying the voltage from 4 to 12 V. The tomato were planted in bucke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
1
8
1
Order By: Relevance
“…Plants irrigated with magnetically-treated water grew taller than those irrigated with untreated water when plants were sampled at 30, 37, 43, 50, 57, 63, and 72 d after transplanting, averaged over all levels of salinity. Similarly, the height of tomato plants irrigated with magnetically-treated water was significantly higher than plants irrigated with untreated water [34]. Using magnetized irrigation water also improved plant stem diameter and plant fresh and dry weight.…”
Section: Discussionmentioning
confidence: 89%
“…Plants irrigated with magnetically-treated water grew taller than those irrigated with untreated water when plants were sampled at 30, 37, 43, 50, 57, 63, and 72 d after transplanting, averaged over all levels of salinity. Similarly, the height of tomato plants irrigated with magnetically-treated water was significantly higher than plants irrigated with untreated water [34]. Using magnetized irrigation water also improved plant stem diameter and plant fresh and dry weight.…”
Section: Discussionmentioning
confidence: 89%
“…Mahjob and Taher, (2005). Huang et al, (2008), Taha et al, (2011), Yusuf and Ogunlela (2015). Khalil et al, (2016)., Khater et al, (2015) and Abd El-Ghaffar-Rania, (2018), Abo batta (2015), Bayoumy et al (2019).…”
Section: Soil Basic Infiltration Rate (Ir)mentioning
confidence: 99%
“…The study found that the stem diameter did not change when watering pear plants with magnetized water. In contrast, different results obtained on other crops such as corn (Alattar, Elwasife, Radwan, & Abuassi, 2019), mustard plants (Jogi, Dharmale, Dudhare, & Aware, 2015), tomatoes (Yusuf & Ogunlela, 2015;. They showed that watering plants with magnetized water positively affected stem diameter.…”
Section: Effect Of Magnetized Water On Stem Diametermentioning
confidence: 90%